Character Strengths and Emotion Self-regulation in Brazilian Workers - Guimarães, Monique A.; Batista, Helder H. V. S.; Pio, Jamile L. S.; Noronha, Ana Paula P. (Anales de Psicología / Annals of Psychology, 2024)
Character strengths and emotion self-regulation are relevant psychological resources to help workers cope with current demands in the workplace. The present investigation aimed to test the association with and the predictive power of the character strengths regarding emotion self-regulation. A total of 203 participants aged 18 to 68 years answered the sociodemographic questionnaire, Character Strength Scale – Brief (CSS-Brief), and the Emotion Self-Regulation Scale – Adult (ESRS-AD). The findings indicated weak to strong associations between the CSS-Brief and ESRS-AD factors. The intrapersonal strength and the intellectual and interpersonal strengths predicted the emotion self-regulation strategies likely to be adopted by the workers. The gathered evidence suggested significant differences in the ESRS-AD and CSS-Brief regarding the participants’ sociodemographic features. These results have occurred regardless of the workers’ hierarchical level and job department.